Laravel Framework-Based Information System of the Department of Information Technology of Universitas Muhammadiyah Yogyakarta - Musyary, Musyary; Kurniati, Aprilia; Damarjati, Cahya (Emerging Information Science and Technology, 2023)
It is crucial to have a reliable and adequate information system to implement information technology. It explains why technology must continue advancing in this area, specifically regarding the Information Technology Department’s information management at Universitas Muhammadiyah Yogyakarta (UMY). Information has been disseminated through the WhatsApp and Telegram applications, leading to improper conveying of the made and supplied information due to excessive stacking. Hence, a web-based information system was developed in PHP with the help of the Laravel framework to overcome the issue. Moreover, a database was set up using MySQL to circumvent the issue. The newly constructed information system could enhance information management, leading to more accurate and efficient information generation for various uses.